Ringworm in rabbits caused by trichophyton mentagrophytes - ΜΠΟΥΡΤΖΗ-ΧΑΤΖΟΠΟΥΛΟΥ Ε.; ΚΟΝΤΟΣ Β. (Journal of the Hellenic Veterinary Medical Society, 2019)
Ringworm enzootics in two big rabbit farms in the Thessaloniki area are reported. The infection first appeared in autumn and continued for many months. In the young weaned animals the disease was severe and the morbidity high (40-50%), While in the adults it was mild and the morbidity low (5-10%). Growth was delayed and the witgt loss was estimated at about 30-40%. Trichophyton mentagrophytes was isolated from skin and hair samples, and from hair, collected from the inside, and from soil collected from the surroundings of the animal house